SONOGRAPHIC ASSESSMENT OF PROSTATE VOLUME IN MEN WITH RAISED PROSTATE-SPECIFIC ANTIGEN (PSA) IN ONITSHA METROPOLIS - Ohagwu, Christopher C.; Nwadike , Sharonrose Ogochukwu; Ugwu , Anthony C.; Elugwu , Chukwuemeka Henry; Ukibe , Nkiru R. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
The prostate-specific antigen (PSA) level is a useful indicator of prostate volume and may inform the choice between treatment options for benign prostatic hyperplasia and other benign conditions. The observation of greater testing of men living in more affluent areas is consistent with previous studies. Therefore, this study was aimed at evaluating the actual volume of the prostate gland in different age groups, in men with raised PSA value. This cross-sectional study was conducted sonographically among men aged 40-89 years in Onitsha Anambra State of Nigeria with clinical indication of raised prostate specific antigen (PSA). Both laboratory and ultrasound procedures were carried out following the standard procedures after obtaining ethical approval from Anambra State of Nigeria Ministry of Health. Data such as age, prostate volume (PV), PSA, total PSA and free PSA were obtained using data capture sheet. The statistical package for social sciences (SPSS) version 20.0. (SPSS Incorporated, Chicago, Illinois). Descriptive (mean, standard deviation, percentage, frequency, and charts) and inferential (Pearson correlation test) statistical tools were adopted for statistical data analysis. The level of statistical significance was set at p < 0.05. The mean and standard deviation for prostate volume were 26.6±7.576 cm3. The mean and standard deviation values for prostate volume at different age group are 24.47±5.438 cm3, 25.06±5.94132 cm3, 28.76 cm3±9.814 cm3 and 27.22±8.0638 cm3 for age group 40-49years, 50-59years, 70-79years and 80-89years of age respectively. There were no statistically significant correlations between TPSA and PV (r=0.003, p= 0.96), and between FPSA and PV (r=0.031, p= 0.66).There were no statistically significant correlations between TPSA and age (r=0.04, p=0.56), and between FPSA and age (r=0.02, p= 0.72). There was a positive statistically significant correlation between prostate volume and age(r=0.21, p=0.002). The study population has normal value of prostate volume. The prostate volume was not significantly influenced by the TPSA and FPSA values. However, the subject’s age has significant positive correlation with the prostate volume. Therefore, in assessing the prostate volume, the age of the individual should be taken highly into consideration.